Intrapancreatic true aneurysm treated by laparoscopic spleen- preserving distal pancreatectomy: Case Report and review of literature. Issue 1 (28th February 2018) - Rashidian, Nikdokht; Faridi, Maziar; Adman, Amir Ashkan; Fahimi, Hossein
No abstract available